Potential protective effect of honey against chronic cerebral hypoperfusion-induced neurodegeneration in rats - Saxena, Anil Kumar; Phyu, Hnin P.; Al-Ani, Imad Matloub Dally; Talib, Norlelawati A. (Anatomical Society of India., 2014)
Introduction: To investigate the neuroprotective potential of Malaysian Tualang honey in chronic cerebral hypoperfusion induced by permanent bilateral common carotid arteries ligation (2VO) in rats. Methods: Rats were randomly divided into three groups (n ¼ 10); sham control, honeyuntreated 2VO group “2VO” and honey treated 2VO group “2VO þ H”. At 10th week of 2VO surgery, all the rat were sacrificed, brains were dissected out, the right hemisphere was processed for histological study, neuronal counts were performed on cresyl violetstained sections, the number of viable neurons in CA-1 region of the hippocampus were analysed and counted. Results: There were damaged, distorted, irregular cells with shrunken cytoplasm and dark pykonotic nuclei in “2VO” rats. Treatment of rats with honey restored the hippocampal cells to their normal structure and reduced loss of neurons in “2VO þ H” rats as compared with “2VO” rats. Discussion: This study shows that Malaysian Tualang honey might have therapeutic potential for the treatment of chronic cerebral hypoperfusion related neurodegenerative disorders